The Role of Echocardiography in Neonates and Pediatric Patients on Extracorporeal Membrane Oxygenation - Bautista-Rodriguez, Carles; Sanchez-de-Toledo, Joan; Da Cruz, Eduardo M. (Frontiers in Pediatrics, 2018)
Indications for extracorporeal membrane oxygenation (ECMO) and extracorporeal cardiopulmonary resuscitation (ECPR) are expanding and echocardiography is an evaluation tool of utmost importance to assess safety, effectiveness and readiness for circuit separation. Echocardiography is key to anticipate complications and improve outcome. Understanding the patient and the ECMO circuit anatomy and physiology for the different modalities support is crucial prior any ECMO echocardiographic evaluation. It is also vital to acknowledge that the usefulness of echocardiography on ECMO patients is not limited to the evaluation of cardiac function and that decisions should not be taken exclusively upon echocardiographic findings. Echocardiography has specific indications and applications but also limitations and these can be defined prior and during cannulation, throughout the ECMO run, upon separation and after separation. The use of specific and consistent echocardiographic protocols for patients on ECMO is recommended.